Seed Production Strategy in Facing Climate Change - Prijadi (Future Science)
Climate change due to current global warming is something that cannot be prevented and is very influential in the agricultural sector, especially in producing horticultural seeds. In producing seeds, there are additional special stages compared to plant cultivation in general. The existence of pollination in hybrid plants, the selection of physiological ripe fruit for seed production, seed extraction to seed drying are very dependent on the climate. Therefore, it is necessary to have a seed production strategy, namely the knowledge to find out the rainfall for this year and the following year in order to adjust the planting time, determine the planting location according to the variety recommendations, modify cultivation techniques to harvest and save the seeds that will be optimal and produce quality seeds. Furthermore, there are also plant breeding strategies in producing new superior varieties that are productive and resistant to climate change.